Ssaki w pokarmie puszczyka zwyczajnego Strix aluco w zachodniej części Nadleśnictwa Skierniewice (środkowa Polska) - Gryz, Jakub; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2017)
The aim of the study was to describe the species diversity of small mammals in the western part of the Skierniewice Forest District (Central Poland) using tawny owl ( Strix aluco ) pellets. The landscape itself is a field and forest mosaic with small forest complexes. Four forest complexes with an area between 70 and 750 ha and surrounded by arable lands as well as loosely scattered buildings were chosen to carry out our work in. Owl pellets were collected in the years 2014–2016 and examined for small mammal remains employing standard protocols. Altogether, we identified 963 items belonging to 17 different mammalian prey species. The most numerous was the yellow-necked mouse, Apodemus flavicollis , which accounted for 33.5% of all identified items. As the second most important group, voles ( Microtus spp.) accounted for 12.8% of all identified mammals. Unfortunately, we were unable to find species considered rare in central Poland, i.e. hazel dormouse, Muscardinus avellanarius , European water vole, Arvicola amphibius and field vole, Microtus agrestis . In overall, the species composition of small mammal assemblages in the studied area was similar to adjacent regions.